(untitled) (Medical Forum Monthly, 2021)
Objective: The goal of this examination was to discover relationship of thrombocytopenia severity with evaluating of esophageal varices in patients of the disease of chronic liver. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Medicine Department of Jinnah Hospital in Lahore from June, 2018 to November, 2018. Materials and Methods: Patients satisfying the incorporation and prohibition criteria were also incorporate for the examination right after taking all the informative consents. Particulars of patients were recorded on a proforma. Detailed history and examination was done for all patients and recorded in same proforma. Laboratory tests were sent including platelet counts. Endoscopy was done and findings were noted. Thrombocytopenia and esophageal varices were labelled as per operational definition. All patients were treated as per hospital protocol. Results: From 215 patients, the lowest age was calculated as 18 years and highest age was 60 years with mean + standard deviation 36.30 + 13.66 years. The minimum platelet count was calculated as 40000 and maximum platelet count was 180000 with mean + standard deviation 122707 + 48500.43. The minimum duration of CLD was calculated as 6 months and maximum duration of CLD was 24 months with mean + standard deviation 14.37 + 5.13 months. There were 48.4% male patients and 51.6% female patients. Thrombocytopenia was present in 36.3% patients while it was not present in 63.7% patients. Esophageal varices were present in 27.9% patients while it was not present in 72.1% patients. Conclusion: Thrombocytopenia was present in 36.3% patients while Esophageal varices was present in 27.9% patients. The important relationship was found between presence of thrombocytopenia and presence of esophageal varices. Effect modifiers also showed significant influence.